2014
DOI: 10.11648/j.sjph.20140201.11
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Kidney Injury in Moroccan Medical Intensive Care Patients: A Regional Prospective, Observational Study

Abstract: Objective: To evaluate the incidence, mortality and influencing factors for the development of Acute Kidney Injury (AKI) at admission or during Intensive Care Unit (ICU) stay. Methods: We conducted a prospective, epidemiological survey, in ICU for two years and the data of 97 patients admitted to ICU for medical illness was analyzed. Patients with AKI were categorized by serum creatinine and urine output into 3 stages. Stage 1 was defined as an absolute increase (within 48 hours) in serum creatinine of more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
(71 reference statements)
3
0
0
Order By: Relevance
“…As in other African [2931] and HI country [1] ICU-based studies, AKI was very common in our cohort and affected nearly two thirds (58.5%) of all patients admitted to the ICU. AKI was associated with male gender, higher severity of illness, more sepsis, longer ICU stay and the need for vasopressors.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As in other African [2931] and HI country [1] ICU-based studies, AKI was very common in our cohort and affected nearly two thirds (58.5%) of all patients admitted to the ICU. AKI was associated with male gender, higher severity of illness, more sepsis, longer ICU stay and the need for vasopressors.…”
Section: Discussionsupporting
confidence: 80%
“…This is the largest prospective African study of AKI in critically ill adults with an HIV seropositive rate of 32.6%. Similar studies include reports from Morocco ( n = 97) [29], the Democratic Republic of Congo (DRC, n = 476) [30] and Egypt ( n = 532) [31]. However, only the DRC study reported HIV prevalence, which was low at 2.9%.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation